Surface Water Pollution around Dhaka Export Processing Zone and Its Impacts on Surrounding Aquatic Environment (Journal of Scientific Research, 2016)
This study based on the physicochemical parameters was conducted in order to determine the pollution status in the aquatic body of Dhaka Export Processing Zone (DEPZ) area. A total of 5 water samples were collected on the basis of their distance from the effluent outlet and were examined. Physicochemical parameters like color, temperature, pH, electric conductivity (EC), total dissolved solid (TDS), total suspended solid (TSS), total hardness, total alkalinity, dissolved oxygen (DO), biochemical oxygen demand (BOD) and chemical oxygen demand (COD) were measured via standard determination method. Physicochemical analyses revealed that most of the water quality parameters exceeded the recommended levels set by the Department of Environment (DoE), Bangladesh. The concentrations were found decreasing with increasing distance from the effluent outlet. A very strong positive correlation was found between BOD and COD in all sampling points. Both BOD and COD values had a strong negative correlation with dissolved oxygen (DO). The results indicated that the surrounding aquatic environment is exceedingly contaminated by various pollutants released from DEPZ which is highly vulnerable for the species on that ecosystem.